Resection enterostomy versus Hartmann’s procedure for emergency colonic resections - Grott, Matthias; Weiß, Christel; Kienle, Peter; Hardt, Julia (International journal of colorectal disease, 2017)
Background: If a primary anastomosis is considered too risky after emergency colon resection either a resection enterostomy or an end stoma with closure of the distal bowel (Hartmann’s procedure) is possible. This study analyzes the rate of restoration of intestinal continuity and other surgical outcomes after resection enterostomy placement versus Hartmann’s procedure for emergency colon resections. Methods: All patients who underwent emergency colorectal resections between August 2009 and June 2014 at the University Medical Center Mannheim were reviewed in regard to therapeutic approach, rate of restoration of bowel continuity, and surgical morbidity after the primary operation and after reversal surgery. Results: Fifty-five patients in whom both studied interventions would have been technically feasible were further analyzed. The rate of revisional surgery was significantly higher in the resection enterostomy cohort after the primary operation. There were no significant differences regarding morbidity, mortality, and the rate of restoration of intestinal continuity. Overall, bowel continuity could be restored in 63% (29/46) of the surviving patients. The median time of surgery of the initial as well as of the reversal surgery was significantly longer in the Hartmann’s group. Five of 13 patients underwent protective ileostomy placement in the Hartmann’s group at the time of the reversal (vs. none in the resection enterostomy group). Conclusions: The bowel continuity can be restored in the majority of patients after emergency colonic resection. Conclusive evidence which surgical option should be preferred when a primary anastomosis is considered too risky - Hartmann’s procedure or resection enterostomy - is still lacking.